2022
DOI: 10.1101/2022.05.22.492996
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diversity, abundance, and host specificity of the human skin associated circular and single stranded DNA virome

Abstract: The human skin is our point of contact with the microbial world, yet little is known about the diversity of the skin virome. Studies of the human skin virome have focused on bacteriophage and double-stranded DNA viral genomes, however, there have been few efforts to characterize circular single-stranded DNA viruses that populate human skin. Here, we evaluate the diversity of the circular single-stranded DNA virome collected across three anatomical skin locations from 60 human individuals with five time-point c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Here, we found a small yet diverse eukaryotic virome with anelloviruses confined to disease. Earlier studies have already indicated that anelloviruses were rarely found on the skin of healthy individuals [44], suggesting a logical relationship with the inflammatory component (i.e., immune cells) present in patients but not healthy individuals. Despite this, it remains unlikely that eukaryotic viruses play an important role in HS pathology, given their low abundance and inability to differentiate between healthy and diseased individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found a small yet diverse eukaryotic virome with anelloviruses confined to disease. Earlier studies have already indicated that anelloviruses were rarely found on the skin of healthy individuals [44], suggesting a logical relationship with the inflammatory component (i.e., immune cells) present in patients but not healthy individuals. Despite this, it remains unlikely that eukaryotic viruses play an important role in HS pathology, given their low abundance and inability to differentiate between healthy and diseased individuals.…”
Section: Discussionmentioning
confidence: 99%
“…STR nDNA profiles obtained from DNA samples in this study suggest it may be possible to recover a DNA profile from an aquatic water sample, however, the DNA profiles show substantial loss of alleles in environmental water, with no alleles recovered after 24 h. This differed from DNA profiles obtained from distilled water, which showed some alleles could be detected up to 840 h. These results support previous research which indicates the type of water can impact the detection of DNA. For example, it has been shown that more alleles could be recovered after 72 h from tissue samples from human ribs maintained in freshwater than tissue maintained in saltwater [ 38 ]. Although only three alleles were detected in environmental water at 24 h, there may still be some forensic utility as the partial profile could be used for exclusionary purposes or to suggest a particular individual is the potential source of the eDNA, warranting further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, DNA can originate from a variety of human tissues and biological fluids, which could have different decay profiles to that seen for blood in this study. With respect to human remains, when they are exposed to environmental water for a prolonged period, the body will experience disarticulation and detachment of soft tissue [ 38 , 39 ]. For this reason, it is not unusual to find small parts of a body distant from the rest of the human remains as a result of water currents and animal interactions [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation